PENGARUH PLP II DI MASA PANDEMI TERHADAP KESIAPAN MAHASISWA PAI UMS MENJADI CALON GURU PROFESIONAL - Mursyida Munashiroh; Istanto Istanto; Ma’arif Jamu’in (Universitas Muhammadiyah Surakarta, 2021)
The profession of a teacher is one of the important roles in the world of education. a professional and competent teacher is needed in improving the quality of an educational institution. A teacher before teaching must have mature teaching readiness. Readiness is the most important thing and must be considered when someone does something, including teaching. Many factors affect the readiness of students to become teachers. One way to hone the teaching competence of prospective teacher students to become professional teachers is to take part in the School Field Introduction (PLP) activity. The purpose of this study was to describe the effect of PLP II during the pandemic on the readiness to become professional teacher candidates for the 2017 UMS PAI students This type of research was quantitative using a Likert scale 1-5 questionnaire and qualitative as the reinforcing data. The sample in this study included the 2017 UMS PAI students and was analyzed using SPSS software version 22. The results of this study conclude that the influence of PLP II (X) on student readiness to become professional teachers (Y) has a significant effect, with the significance value of the PLP II influence variable (X) on student readiness to become professional teachers (Y) worth 0.000 0.05 with a count of 11,871.